EXPENSES OF THE KNOWLEDGE-BASED SOCIETY IN THE FUNCTION OF COMPETITIVENESS GROWTH OF BOSNIA AND HERZEGOVINA - Jović, Ljiljana; Vuković, Marija; Ćeranić, Dragana (International Journal of Economic Practice and Policy, 2018)
The aim of the paper is to point out to the status, significance and benefits that Bosnia and Herzegovina has from the development of a knowledge-based society. Comparative analysis of key statistical indicators has shown that Bosnia and Herzegovina is in a very poor position compared to other countries, both in terms of investment in knowledge and innovation according to UNESCO statistics and competitiveness, as indicated by the Word Economic Forum and The Global Competitiveness Report. Bosnia and Herzegovina is also far below the performance of the countries of the European Union whose accession it is striving for. The results of the analysis suggest that investments in the development of science, education and innovation in Bosnia and Herzegovina are so low that they do not show correlation with economic growth and foreign investment flows as key indicators of competitiveness.